Screening of a-amylase/trypsin inhibitor activity in wheat, spelt and einkorn by high-performance thin-layer chromatography - Müller, Isabel; Schmid, Bianca; Bosa, Loredana; Morlock, Gertrud Elisabeth; Justus Liebig University Giessen (My University, 2024)
α-Amylase/trypsin inhibitor proteins (ATI) are discussed as possible triggers for non-celiac gluten sensitivity. The potential of high-performance thin-layer chromatography (HPTLC) was studied for the first time to analyse the inhibitory properties of ATIs from flour of wheat, spelt, and einkorn. Inhibition by each flour of the digestive enzymes trypsin or α-amylase was determined by the reduction of released metabolisation products in comparison to non-digested flour, and positive (acarbose) and negative (water) controls. Firstly, amylolysis was carried out in miniaturized form on the HPTLC surface (HPTLC-nanoGIT) after in-vial pre-incubation of the amylase with the inhibitors from flour. α-Amylase inhibition was evident via the reduction of released saccharides, as analysed by normal phase HPTLC. A strong influence of the flour matrix on the assay results (individual saccharides) was evident, caused by an increased amylolysis of further polysaccharides present, making HPTLC analysis more reliable than currently used spectrophotometric sum value assays. The detection and visualization of such matrix influence helps to understand the problems associated with spectrophotometric assays. Only maltotriose was identified as a reliable marker of the amylolysis. The highest α-amylase inhibition and thus the lowest saccharide response was detected for maltotriose in refined spelt, whereas the lowest α-amylase inhibition and thus the highest saccharide response was detected for maltotriose in refined wheat. A comparison of refined and whole grain flours showed no clear trend in the responses. Secondly, trypsin inhibition and proteolysis were performed in-vial, and any inhibition was evident via the reduction of released peptides, analysed by reversed-phase HPTLC. Based on the product pattern of the proteolysis, einkorn and whole wheat showed the highest trypsin inhibition, whereas refined wheat and refined spelt showed the lowest inhibition. Advantageously, HPTLC analysis provided important information on changes in individual saccharides or peptides, which was more reliable and sustainable than spectrophotometric in-vial assays (only sum value) or liquid column chromatography analysis (targeting only the ATI proteins).
Keywords: ddc:640; ddc:360